Development and validation of the socially shared regulated learning questionnaire: insights from a second-order confirmatory factor analysis - Yang, Yongkang; He, Zhenni; Wei, Yinuo; Tang, Erlong (Frontiers in Psychology, 2025)
This study addresses a critical methodological gap by developing and validating a psychometrically robust, multidimensional socially shared regulated learning (SSRL) questionnaire. Grounded in contemporary theories of collaborative learning and regulation, the questionnaire comprises four theoretically informed dimensions: Shared Goal Setting and Planning, Shared Monitoring and Control, Shared Reflection and Evaluation, and Shared Motivational and Emotional Regulation. Employing a two-phase methodological design, the study first refined questionnaire items through a think-aloud protocol (TAP) with a diverse student sample. Subsequently, the refined instrument was administered to 378 university students, and its structural validity and reliability were evaluated via second-order confirmatory factor analysis (CFA). Results demonstrated excellent internal consistency (ω ≥ 0.82 for all dimensions), robust model fit (CFI = 0.951; RMSEA = 0.050; SRMR = 0.038), and strong hierarchical relationships between dimensions and the overarching SSRL construct. This validated questionnaire provides educators and researchers with an effective, scalable tool for assessing collaborative regulation processes, thus offering insights into enhancing collaborative learning outcomes in diverse educational contexts.